Myanmar’s Travel Behavior, Media Exposure and Perception on Thai cultural Universals - Chokriensukchai, Kanchana (University of the Thai Chamber of Commerce Journal Humanities and Social Sciences, 2014)
This study examines (a) travel behavior, (b) media exposure, and (b) opinions of Myanmar nationals on Thai cultural universals, and aims to create awareness that stimulates a demand for travel in Thailand. The study was conducted with the concept of creating a perception of what can make travel more desirable for a person already familiar with the country, since people are generally drawn to the familiar or that which is consistent with their attitudes (Rogers, 2003). This study relied on the concept of cultural universals proposed by anthropologist Murdock (1945 cited in Shepard, 2010: 81) in order to measure perception consistently. A sample of 385 people were surveyed in Myanmar. The survey found that Myanmar residents travel in the country or abroad with family or friends 1-2 times a year and most of them like nature tourism. Their travel information was gained through personal media searches. Most of them agreed that Thai food could create a perception of Thai tourism among the people of Myanmar. On a visit to Thailand, they would prefer a trip with the purpose of attending classes on campus or in school.